Comparison of AM-PM and DHI records - James R. Dunham (Kansas Agricultural Experiment Station Research Reports, 1985)
A comparison was made of the AM-PM production testing program with the traditional DHI program during 13 test periods of 1984 in the KSU Dairy Teaching and Research Center herd. Although there were slight variations in daily milk weights and percentages of fat and protein in milk, rolling herd averages were nearly identical. Individual 305-2X-M.E. milk and fat records also were compared for 107 cows using both testing programs. Differences between testing programs were minimal) as most records varied by less than 1%. Therefore, it was concluded that the AM-PM program is a very accurate production test.; Dairy Day, 1985, Kansas State University, Manhattan, KS, 1985;
Keywords: Kansas Agricultural Experiment Station contribution; no. 86-94-S; Report of progress (Kansas Agricultural Experiment Station); 484; Dairy; DHI Records; AM-PM Production testing program